The Role of PPKn Teachers in Fostering National and Civic Awareness at Budisatrya Senior High School, Medan - Ayu Lestari; Syarbaini Saleh (MASI Mandiri Edukasi, 2025)
This study examines the role of Pancasila and Citizenship Education (PPKn) teachers in enhancing students’ national and state awareness at SMA Budisatrya Medan. Using a descriptive qualitative method, data were collected from one principal, one PPKn teacher, ten students, and two staff through interviews, observations, and documentation. Results show that most students demonstrated a moderate level of awareness, with weaknesses in discipline, social responsibility, and consistency in applying Pancasila values. Globalisation, social media, low motivation, and limited support from family and school influenced low awareness. PPKn teachers played key roles as role models, facilitators, and motivators, using strategies such as contextual learning, project-based learning, discussions, and extracurricular activities to internalise national values. This study contributes to civic education by showing how contextual and participatory approaches strengthen students’ national identity. It recommends teacher training, digital-based civic projects, and stronger school–parent collaboration to reinforce nationalism in the digital era.